THE EFFECT OF USING ELSA (ENGLISH LANGUAGE SPEECH ASSISTANT) SPEAK APPLICATION ON STUDENTS’ SPEAKING ABILITY FOR THE ELEVENTH GRADE OF MAS DARUL AL MUHAJIRIN IN THE ACADEMIC YEAR 2021/2022 - Puja Aswaty; Ayu Indari (STKIP Budidaya Binjai, 2022)
This research was conducted to the eleventh grade students of of MAS Darul Al Muhajirin in the academic year 2021/2022. This was an experimental research which used two group pre-test and post-test designs. The sample of research was 40 divided by two classes, XI-MIPA 2 as experimental class and XI-MIPA 1 as control class. This research was conducted to know the positive effect of using ELSA Speak Application on students’ speaking ability. Based on the students’ problems such as students worked hard to produce the English expression, students pronounced the words of the expression in inexact way, student used wrong intonation and stress in sounding the English expression. Having analyzed the data of pre-test and post-test by using t-test, from the result of calculation, it was obtained the value of the t-test was 10,619. The degree of freedom is 38 (df = because there was not df 38 in the t-table, so the writers decide to use df 40 since it was closer to 38 that df 30. The table at df 40 showed that the value of t-table ( was 2,02 for 5% and 2,70 for 1%. This result meant that the value of t-test was not appropriate with the criteria of acceptance of Ho, because the fact showed the value of t-test was higher than t-table (2,02 < 10,619 > 2,70). So, from that explanation, writers concluded that null hypothesis was rejected and alternative hypothesis was accepted. Hence, hypothesis stated that there was a significant effect of using ELSA (English Language Speech Assistant) Speak Application on students’ speaking ability for the eleventh grade of MAS Darul Al Muhajirin in the academic year 2021/2022.